Phoenix Diagnostic Clinic - Asuncion, Keziah Ann P.; Bayan, Hershey C.; Centeno, Christabelle P.; Galicia, Cesar Eduardo M.; Gutierrez, Raymond V.; Nuque, Vivien Gem I.; Villalobos, Rochelle O. and Yabut Jazmine Charlene B. 4 0 16; 5
NO ABSTRACT.
Feasibility Study: (Bachelor of Science in Accountancy) - Pamantasan ng Lungsod ng Maynila, 2014.
Keywords: 2 -- 0; 6; 20; 20; 2